Evaluasi Performa Lapisan AC-BC Akibat Eksposur tanpa Penutupan AC-WC - Hasrul, Reza; Saraswati, Rizki Ayu; Rahman, Mohammad Junaedy; Yusuf , Furqan Ali; Haedar, Ahmad Wahidiyat; Iriandy; Mahmuda, Ali Fauzi (Jurnal Teknik Sipil MACCA, 2025)
This study evaluates the impact of exposure on the Asphalt Concrete – Binder Course (AC-BC) layer without the Asphalt Concrete – Wearing Course (AC-WC) overlay over two years on its mechanical properties and density. Exposure to traffic loads and environmental conditions, such as UV radiation, rainfall, and temperature fluctuations, potentially causes significant degradation. Samples were tested using the Marshall method to analyze stability, flow, air voids, VMA, VFB, and Marshall Quotient, with field data compared to initial laboratory data before. The results indicate a reduction in relative density from 98% to 92–94%, as well as changes in aggregate gradation, particularly in the medium and coarse fractions. Stability was recorded at 3709.99 kg, significantly exceeding the minimum specification of 800 kg, but the flow of 5.77 mm exceeded the 2–4 mm specification range, suggesting a higher tendency for plastic deformation. This study emphasizes the importance of promptly covering the AC-BC with AC-WC to prevent further degradation. Recommendations include the application of a seal coat as a temporary mitigation measure. These findings offer strategic insights for more efficient and durable road infrastructure planning.